Realization of three-dimensionally MEMS stacked comb structures for microactuators using low-temperature multi-wafer bonding with self-alignment techniques in CMOS-compatible processes - Teo, Adrian J. T. (2022)
A high-aspect-ratio three-dimensionally (3D) stacked comb structure for micromirror application is demonstrated by wafer bonding technology in CMOS-compatible processes in this work. A vertically stacked comb structure is designed to circumvent any misalignment issues that could arise from multiple wafer bonding. These out-of-plane comb drives are used for the bias actuation to achieve a larger tilt angle for micromirrors. The high-aspect-ratio mechanical structure is realized by the deep reactive ion etching of silicon, and the notching effect in silicon-on-insulator (SOI) wafers is minimized. The low-temperature bonding of two patterned wafers is achieved with fusion bonding, and a high bond strength up to 2.5 J/m2 is obtained, which sustains subsequent processing steps. Furthermore, the dependency of resonant frequency on device dimensions is studied systematically, which provides useful guidelines for future design and application. A finalized device fabricated here was also tested to have a resonant frequency of 17.57 kHz and a tilt angle of 70° under an AC bias voltage of 2 V.